2010
DOI: 10.1186/1756-9966-29-116
|View full text |Cite
|
Sign up to set email alerts
|

Elevated c-Src and c-Yes expression in malignant skin cancers

Abstract: AbstractsBackgroundSrc family kinases (SFKs) play an important role in cancer proliferation, survival, motility, invasiveness, metastasis, and angiogenesis. Among the SFKs, c-Src and c-Yes are particularly over-expressed or hyper-activated in many human epithelial cancers. However, only a few studies have attempted to define the expression and role of c-Src and c-Yes in cutaneous carcinomas.ObjectivesTo investigate the expression of c-Src and c-Yes in cutaneous carcinomas to include malignant melanoma (MM), sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 14 publications
(13 reference statements)
0
39
0
Order By: Relevance
“…In addition to known GBM-associated proteins, novel potential biomarkers identified in this study include CLIC4, NP1L1, IGKC, TAGL2, and YES (Supplementary Table S1). These proteins have been identified to be involved in processes promoting cancer progression but have never been previously associated with GBM (35,36,60,63,65). With further validations, these proteins may serve as novel therapeutic targets in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to known GBM-associated proteins, novel potential biomarkers identified in this study include CLIC4, NP1L1, IGKC, TAGL2, and YES (Supplementary Table S1). These proteins have been identified to be involved in processes promoting cancer progression but have never been previously associated with GBM (35,36,60,63,65). With further validations, these proteins may serve as novel therapeutic targets in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…SRC is the first cloned oncogene, and significant literature implicates SRC in human cancer, especially in skin SCC (Matsumoto et al 2003;Lee et al 2010;Sudol 2011). Nevertheless, the mechanisms of SRC oncogenic activity are still poorly understood, as the essential SRC phosphorylation targets responsible for cellular transformation have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…5 and 6. DISCUSSION c-Yes, similar to other members of the SFKs (e.g., c-Src), is a (proto)oncogene, with its expression intimately related to carcinogenesis (11,29,53,57,58). For instance, overexpression of c-Yes in human colorectal carcinoma cells promotes metastatsis (3), but recent studies have shown that it also plays critical roles in different cellular physiological function, such as growth factor activation, endocytic vesicle-mediated protein trafficking, and cell signaling (11,15,68,69).…”
Section: Knockdown Of C-yes In the Testis In Vivo Disrupts Distributimentioning
confidence: 99%
“…c-Yes (or Yes 1, Yamaguchi sarcoma viral oncogene homolog 1), a nonreceptor protein tyrosine kinase and a member of the Src family kinases (SFKs) and also a proto-oncogene whose expression is upregulated in various cancers, including melanoma (29), colon cancer (58), and brain cancer (53), is also known to be involved in regulating cell cycle and cytokinesis (28). In fact, members of the SFKs are targets of chemotherapy (1,67).…”
mentioning
confidence: 99%